This Monastic Moment: The War of the Spirit & the Rule of Love by John W de Grucy - Ullrich, Calvin (Stellenbosch Theological Journal, 2023)
Diagnosing a cultural mood is never easy, not least because our times are marked by a volatility where one can scarcely hold onto anything in the maelstrom of conflicting currents. Here, in South Africa, ‘morbid symptoms’ are painfully being felt in an interregnum where a genuinely new future seems perennially deferred with every crisis that seems to pile upon the last. But a cultural mood is not the same thing as a theological or indeed monastic moment. What, then, is unique about a specifically Christian response when pessimism or enclavist retreat are the order of the day and where hope is in such short supply? The eminent theologian John de Gruchy, with characteristic perspicuity enters this malaise with a composed but urgent plea for us to “listen again” to what the “Spirit is saying.” This academically astute but readable text journeys through themes and figures (Calvin, Barth, Bonhoeffer, and Merton, among many others) which have distinguished de Gruchy’s career as a public theologian, while he casts his net into the far reaches of Christianity’s early history up to the present, offering an absorbing narrative whose golden thread is that of monasticism.